Generalizing visual fast count estimators for underwater video surveys. Issue 12 (7th December 2015) - Barry, Jon; Eggleton, Jackie; Ware, Suzanne; Curtis, Matthew
Abstract : A generalized Visual Fast Count (GVFC) method of moments estimator is proposed for estimating epifaunal species abundance from underwater video survey transects. This formalises and provides a statistical framework for previous ad‐hoc Visual Fast Count methods. For a single transect, we derive the expected value of the naive GVFC estimator and use this to create the method of moments estimator, which has reduced bias. A maximum likelihood estimator for multiple transects is derived. For illustration, our methods are applied to a series of video trawls at Folkestone Pomerania in the Dover Straits, UK. Although our methods have been developed for marine applications, they could also be applied to some terrestrial transect surveys.